Contested Surveillance: Gendered Citizenship and Political Participation in Egypt and Lebanon - Zarif, Mohamad (AUC Knowledge Fountain, 2026)
While the 2011 Arab Uprisings were famously framed by the utopian narrative of a 'Facebook Revolution', this view has given way to a dystopian reality in which digital infrastructures can facilitate authoritarian retrenchment. This thesis interrogates how lowermiddle- and working-class precarious youth navigate and perceive this "Architecture of Control" in Cairo and Beirut. Using a comparative qualitative design with purposive and snowball sampling, this research integrates digital ethnography and fourteen interviews with eighteen participants (nine women, seven men) to capture lived experiences of surveillance rather than the internal logic of state security institutions. The study yields three primary findings. First, urban mobility is governed by spatial fragmentation, requiring youth to negotiate checkpoints, neighborhood watchers, family scrutiny, and sectarian territoriality. Second, this architecture is profoundly gendered. The digital sphere relies on "lateral surveillance" (Andrejevic, 2005), where vigilant audiences police moral boundaries, subjecting young women to online harassment that severely curtails their public participation (Trottier, 2017). Third, youth agency has shifted from the politics of the square to tactics of evasion, avoidance, and everyday survival. By navigating blind spots and curating digital selves, the precariat practices negotiated citizenship rather than open revolt. Ultimately, youth experience and perceive surveillance not merely as institutional policy, but as an inescapable atmosphere (Standing, 2021). Consequently, citizenship mutates into a gendered "performative tactic" (Isin, 2008; Bayat, 2013): a daily negotiation of perceived visibility to sustain physical and social survival (Sobhy & Abdalla, 2024). Illuminating these tactics shows the need for rights-based privacy policies and spatial interventions to safeguard civic life for marginalized Middle Eastern youth.